Analisis Ekonomi Kesehatan Rumah Tangga Indonesia Pada Masa Pandemi Covid-19 - Devi Indah Erlita; Asyifa Nur Azizah; Yuhka Sundaya (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2022)
The decreasing household access to health services occurred during the Covid-19 pandemic. Observing the health profile of BPS Indonesia (2021), it can be seen that there is a percentage change in the decrease in road treatment and an increase in health complaints. This study aims to present the results of estimating econometric models that explain economic and non-economic variables that can potentially change the opportunities for health demand in Indonesia. The morbidity data for each district and city on the selected island was converted into four categories of health status, namely [1] very healthy, [2] healthy, [3] moderately healthy, and [4] unhealthy. This research is deductive. We use the demand for health theory to identify variables that need to be researched and employ QLDV (qualitative limited dependent variable) to estimate them. The estimation results are conducting to the issue of efforts to increase the chances of household health levels and serial studies starting in 1972. The simulation results with marginal effect predict that the probability of demand for health will increase by 2.71 percent in conditions of inflation of food and health commodities at the level of 6 and 7 percent, children under-five immunization coverage is close to 90 percent, education average is junior high school, income allocation of less than 50 percent, and real income per capita is close to 10 million per year. Regarding the literature series, this study succeeded in showing the significance of health commodity prices which was difficult to display by previous researchers.